P.J. funnybunny camps out - Sadler, Marilyn (Canada : Random house, 1993)
Although P.J. and his friends refuse to let donna duck ans honey bunny go camping with them because"Camping is not for girls," the girls follow and get proof that camping is hard to work even for boys.
Keywords: Camping - fiction; Animals - fiction